Effective contingency plan framework for risk management in the operation and maintenance of Malaysian highway tunnel - Lee, Yong Siang (2020)
Highway tunnel projects are indispensable during the installation of new infrastructures despite their unique characteristics and potential applications. Yet, it is not uncommon for any risks to occur especially during the operation and maintenance stage. Over the past few decades, a lot of major accidents and disasters occurred and the re-occurrences of similar major risk incidents which even showing criticality for highway tunnel operator to manage the risks effectively. Unfortunately, the traditional risk management plan is insufficient to manage residual or unforeseeable risks. Therefore, this research aims to develop an effective contingency plan framework from gaps identified in the current practices for risk management in the operation and maintenance of Malaysian highway tunnel. The selected case study for this research is based on Meru-Menora Tunnel that located along North-South Expressway near Jelapang, Perak at KM260.00. In the case study, there are several data collection techniques include secondary data collection, focus group interview, actual site observation, and Analytical Hierarchy Process (AHP) were employed. Twenty-six (26) sub-risks which fall under five (5) main risks; drainage-related, pavement-related, slope-related, tunnel structure-related and other structure-related risk were identified. An Analytical Hierarchy Process (AHP) expert survey was conducted to determine the priority ranking of all the sub-risks. The results revealed that seven (7) critical sub-risks with highest ranking; slope failure, tunnel structure failure, contingency maintenance works due to slope risk, cost overrun in operation due to slope risk, drainage flood risk, contingency maintenance works due to tunnel structure risk and contingency maintenance works due to drainage risk. All the critical sub-risks have great potential to influence the operation and maintenance of Meru-Menora Tunnel which should be managed properly. The current risk management practices were investigated and evaluated. A contingency plan framework was developed and validated by Delphi Technique. There are several strategies used in the contingency plan framework include the introduction of new and effective risk management practice methods, the improvement of frequency of current risk management practices where appropriate and the suggestion of a new contingency plan for those risks without risk response plan. The future research can be tested in other Malaysian highway tunnels.